Molecular and Hematological Insights into Chronic Enterobius vermicularis Infections and Emphasis on Mitochondrial COX1 Gene Profiling: A Systematic Review and Meta Analysis - Mnazzal, Ameerah Hameed; Jasim , Amani M.; Mohammed, Taghreed Khudhur (House of Wisdom: Journal on Library and Information Sciences, 2025)
Background: The human pinworm, or Enterobius vermicularis, is a very common intestinal nematode that infects an estimated 400 million individuals globally, especially school-age children. Despite being regarded as a relatively minor parasitic infection, there is growing evidence that infections that are recurring or chronic may have more substantial consequences on the host's immunological, hematological, nutritional, and metabolic condition. Additionally, the utilization of mitochondrial genes, such as cytochrome c oxidase subunit 1 (cox1), has improved diagnostic accuracy and enabled a deeper comprehension of parasite variety and epidemiology studies to molecular advancements. Methods: Several important databases, including PubMed, Scopus, Web of Science, and the Cochrane Library, were used for this systematic review. A mix of Medical Subject Heading phrases (MeSH terms) and keywords pertaining to intestinal nematodes, pinworms, Enterobius vermicularis, the host's immune system, hematological conditions, cytochrome c oxidase subunit 1 (cox1), and elementary school students were used in the search. Only published works in English that were released between January 2, 2018, and June 1, 2025, were included in the study. Results: from 2018 to 2025, a systematic review on Enterobius vermicularis followed PRISMA guidelines, identifying 1,320 records from databases and other sources. After removing 270 duplicates, 1,050 unique studies were screened by title and abstract, with 850 excluded for irrelevance. Of the 200 full-text articles reviewed, 140 were excluded for various reasons, leaving 60 studies for qualitative synthesis. Among these, 40 had sufficient data for meta-analysis. This structured and rigorous process ensured high-quality evidence on the prevalence, diagnosis, and clinical impact of E. vermicularis in children. Conclusions: Knowing the wider ramifications of an infection caused by Enterobius vermicularis goes beyond its typical manifestation. Because of its high prevalence and capacity to affect immune cell numbers, micronutrient levels, and even metabolic balance, it continues to be important in parasitology and public health. More accurate research on epidemiology, transmission, and resistance are made possible by molecular approaches like cox1 gene analysis, which offer strong instruments for precise identification. Highlights: Chronic E. vermicularis infections may influence immune function, blood parameters, and nutritional balance in children. A PRISMA-based systematic review of 1,320 records yielded 60 qualitative studies and 40 for meta-analysis, ensuring evidence quality. Molecular Advancements, Use of the cox1 gene improves species identification and helps track parasite diversity and resistance patterns. Keywords: Enterobius Vermicularis, Intestinal Nematode, cox1 Gene, Pediatric Parasitology, Molecular Diagnosis